Potential of Reduction Solid Waste from Office Building (Case Study: Gedung Polda Jambi) - Laura, Winny; Galih, Ira; Lovena, Anri (BERKALA SAINSTEK, 2023)
Solid waste management in building can be managed with the waste management policy and waste management practice tools. It is contained in the concept of green building. The purpose of this study was to analyze the potential reduce of solid waste in office buildings which is managed by waste management policy and waste management practice tools, and provide scheme recommendations for solid waste management for office buildings the object of this study is Jambi Regional Police Office Building. The methodology was a survey method with solid waste sampling (SNI 19-3964-1994) in Building A, Building B, Canteen and Garden Area and Parking The sampling did for 8 days. Quantitative and quantitative parameters were obtained from the calculation of the generation and composition of solid waste, and also interviews. The results for the generation of solid waste on Jambi Regional Police Office Building: 40.40 kg/day or 0.027 kg/person.day (consist of 45% organic, 28% inorganic, 26% paper and B3 0.7% and others 0.3%). Recommendations scheme can be given for solid waste management in the form of the application of waste management practice tools are started from modification of the waste into separate, collection is done as often as possible, solid waste treatment is done composting and sales to waste banks. The potential for reducing solid waste if the waste management policy and practice tools are applied is 85.64% to 5.8 kg/day.